2023
DOI: 10.1002/mde.3981
|View full text |Cite
|
Sign up to set email alerts
|

Climate policy uncertainty and corporate green innovation performance: From the perspectives of organizational inertia and management internal characteristics

Abstract: The impact of policy uncertainty caused by climate change has attracted widespread attention, but there are few studies on the relationship between climate policy uncertainty and corporate green innovation performance. This paper uses a sample of the A‐share listed companies in Shanghai and Shenzhen from 2007 to 2020 to explore the impact of climate policy uncertainty on corporate green innovation performance. And this paper also studies the moderating effect of organizational inertia and the joint moderating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Similarly, investment regarding R&D and acquiring patents will discourage managers in a high CPU situation. In brief, literature supports that CPU inversely affects RIP (Bai et al, 2023;Huo et al, 2023). Furthermore, extending such logics to our context, we may hypothesize that H1.…”
Section: Empirical Review and Hypothesis Developmentsupporting
confidence: 55%
See 2 more Smart Citations
“…Similarly, investment regarding R&D and acquiring patents will discourage managers in a high CPU situation. In brief, literature supports that CPU inversely affects RIP (Bai et al, 2023;Huo et al, 2023). Furthermore, extending such logics to our context, we may hypothesize that H1.…”
Section: Empirical Review and Hypothesis Developmentsupporting
confidence: 55%
“…This negative impact can be explained as high EPU leads to deter private sector investments aimed to enhance the innovation within the country. In the high CPU era, businesses and private investors may feel hesitation to allocate resources for R&D when they are unsure about the regulatory environment, making the expansion of innovative technologies more difficult (Huo et al, 2023;Liu et al, 2023). Moreover, an increase in climate uncertainty can lead to risk aversion among investors and innovators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of academic studies have examined several factors in corporate innovation. Most of the above studies focused on the examination of innovation inputs, specifically R&D investments, as well as innovation outputs, primarily represented by patents (Huo et al, 2023;Lin & Lu, 2023). The conclusions are mixed.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, existing studies have demonstrated from the perspectives of corporate investment (Huang, 2023) and corporate value (Naseer et al, 2023) that the rise of CPU may have adverse effects on enterprises. Additionally, the impact of CPU often outweighs that of the economic policy uncertainty commonly known to people (Huo et al, 2024). These factors endow the study of the relationship between CPU and corporate greenwashing with deeper practical significance.…”
Section: Introductionmentioning
confidence: 99%